ANALISIS SPASIAL PERUBAHAN AREA TERBANGUN KOTA GORONTALO (Spatial Analysis Of Gorontalo City Building Area Changes) - Muhammad Rijal Syukri; Sri Sutarni Arifin (Universitas Muhammadiyah Gorontalo, 2018)
Abstract - Development in urban areas growth accompanied by increasing population. This increase has an impact on the increasing need for urban space. This causes the area to be built in urban areas to increase and the reduction of open space so as to encourage the use of rice fields as residential areas and offices. Therefore it is necessary to do a study or evaluation through spatial analysis to determine changes in the use of paddy fields in Gorontalo City in a certain period of time. This study is one of the references in the direction of environmentally sound development for the future. This study aims to analyze changes in land use as a built area within 5 years from 2008 to 2013. The method used in this study is spatial analysis consisting of image data and digital maps as supporting data. The analysis was carried out by overlaying the land use map technique with different periods of time from the interpretation of digital satellite images. The results showed that there were two types of changes in the built-up area in Gorontalo City within a period of 5 years, namely the change in open area to a built area and the area built into an open area. Keywords: changed, land, built area, gorontalo Abstrak – Pembangunan di wilayah perkotaan terus berkembang yang disertai dengan meningkatnya jumlah penduduk. Peningkatan ini berdampak pada semakin tingginya kebutuhan akan ruang kota. Hal ini menyebabkan kawasan terbangun di wilayah perkotaan semakin meningkat dan berkurangnya ruang terbuka sehingga mendorong penggunaan lahan sawah sebagai area permukiman dan perkantoran. Oleh karena itu perlu dilakukan kajian atau evaluasi melalui analisis spasial untuk mengetahui perubahan pemanfaatan lahan sawah yang ada di Kota Gorontalo dalam kurun waktu tertentu. Kajian ini merupakan salah satu acuan dalam arahan pembangunan yang berwawasan lingkungan untuk masa mendatang. Penelitian ini bertujuan untuk menganalisis perubahan pemanfaatan lahan sebagai area terbangun dalam kurun waktu 5 tahun dari tahun 2008 hingga 2013 . Metode yang digunakan dalam penelitian ini adalah analisis spasial terdiri dari data citra dan peta digital sebagai data pendukung. Analisis dilakukan dengan teknik overlay peta penggunaan lahan dengan kurun waktu berbeda hasil interpretasi citra satelit digital. Hasil penelitian menunjukkan terdapat dua jenis perubahan area terbangun di Kota Gorontalo dalam kurun waktu 5 tahun yaitu perubahan area terbuka menjadi area terbangun dan area terbangun menjadi area terbuka. Kata kunci: perubahan, lahan, area terbangun, gorontalo